Functional diversification of oxalate decarboxylases in terms of enzymatic activity, morphosporogenesis, stress regulation and virulence in Colletotrichum siamense - Lv, Yanyun; Liu, Yu; Lin, Yuqing; Zheng, Huiying; Yan, Jingting; Zhang, Yu; Miao, Weiguo; Wu, Wei; Lin, Chunhua (Frontiers in Microbiology, 2025)
Oxalate decarboxylase (OxdC) is an enzyme that degrades oxalic acid and may affect the virulence of necrotrophic fungal pathogens that rely on oxalic acid as a pathogenicity factor. However, the biological function of OxdCs in hemibiotropic fungi is still unknown. Our previous studies revealed four OxdC-encoding genes in the whole genome, with CsOxdC3 playing important roles in morphosporogenesis, fungicide resistance and virulence in Colletotrichum siamense. Here, we systematically analyzed the biological functions of four oxalate decarboxylase genes in C. siamense via a loss-of-function method. The results revealed CsOxdC1, CsOxdC2, and CsOxdC4 played major roles in degrading oxalic acid in C. siamense, whereas CsOxdC3 did not. All four CsOxdCs positively modulated morphosporogenesis, including vegetative growth, conidial size, conidial germination rate and the appressorium formation rate, to different extents. In particular, the CsOxdC3 deletion mutant failed to form appressoria. The four OxdC gene deletion mutants had different responses to Mn2+, Cu2+, and multiple fungicides. Among them, CsOxdC2 and CsOxdC4 exhibited positive roles in resistance to Mn2+ and Cu2+ stresses; CsOxdC1 played a slightly positive role in C. siamense resistance to azole fungicides; and CsOxdC3 had a significantly positive role in regulating the sensitivity of C. siamense to multiple fungicides, including pyrrole and azole, but not CsOxdC2 and CsOxdC4. Furthermore, compared with the wild-type strain, ΔCsOxdC2 and ΔCsOxdC3, but not ΔCsOxdC1 and ΔCsOxdC4, displayed significantly reduced virulence. In conclusion, our data indicated that CsOxdCs exerted diverse functions in morphogenesis, stress homeostasis, fungicide resistance, and virulence in C. siamense. This study provides insights into the biological function of OxdCs in the hemibiotrophic fungus C. siamense.